2010
DOI: 10.1620/tjem.222.113
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Stem Cells Differentiate into Sinus Node-Like Cells

Abstract: The advent of stem cell therapy brings about the hope to restore the loss of cardiac pacemaker cells. However, it is largely unknown whether cardiac stem cells are able to differentiate into pacemaker cells. The purpose of this study was to determine whether the heart of large juvenile mammals contains cardiac stem cells (CSCs), which are suitable as seed cells for restoration of cardiac pacemaker cell. The c-kit + CSCs were isolated from one-month-old mongrel dogs. CSCs that we sorted were self-renewing, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Cells that are generated from cardiac tissue, express c-kit and differentiate into numerous cell lineages may be regarded as CSCs. A recent study conducted by the authors of the present study, showed that c-kit positive CSCs from dog and rat hearts have the potential to differentiate into sinus node-like cells in vitro ( 3 ). However, the proportion of sinus node-like cells was small and the intrinsic mechanisms behind this kind of differentiation remain to be elucidated.…”
Section: Introductionmentioning
confidence: 64%
“…Cells that are generated from cardiac tissue, express c-kit and differentiate into numerous cell lineages may be regarded as CSCs. A recent study conducted by the authors of the present study, showed that c-kit positive CSCs from dog and rat hearts have the potential to differentiate into sinus node-like cells in vitro ( 3 ). However, the proportion of sinus node-like cells was small and the intrinsic mechanisms behind this kind of differentiation remain to be elucidated.…”
Section: Introductionmentioning
confidence: 64%
“…Furthermore, Lian and colleagues robustly generated directed differentiation cultures with yields of up to 98% CMs by sequential treatment with a small molecule Wnt agonist, CHIR99021, followed by a small molecule Wnt antagonist, Wnt inhibitor of Wnt production 4 (IWP4) [26,27]. More recently, differentiation strategies further manipulating cellular signaling have shown control over individual cardiac cell types such as atrial, ventricular and nodal cells [2830]. …”
Section: Mimicking Heart Development In Vitromentioning
confidence: 99%